2017
DOI: 10.1038/tp.2017.213
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of AMBRA1-related autistic features in human and mouse

Abstract: Ambra1 is linked to autophagy and neurodevelopment. Heterozygous Ambra1 deficiency induces autism-like behavior in a sexually dimorphic manner. Extraordinarily, autistic features are seen in female mice only, combined with stronger Ambra1 protein reduction in brain compared to males. However, significance of AMBRA1 for autistic phenotypes in humans and, apart from behavior, for other autism-typical features, namely early brain enlargement or increased seizure propensity, has remained unexplored. Here we show i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…First, the AMBRA1 SNP rs3802890 genotype showed strong sex specificity in its phenotypic effects, with restriction to females. These results corroborate and extend previous analyses of mice and humans [8, 10, 17], all of which show female-restricted or female-biased effects on psychological, psychiatric, and neurological phenotypes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, the AMBRA1 SNP rs3802890 genotype showed strong sex specificity in its phenotypic effects, with restriction to females. These results corroborate and extend previous analyses of mice and humans [8, 10, 17], all of which show female-restricted or female-biased effects on psychological, psychiatric, and neurological phenotypes.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Mitjans et al [10] showed that the AMBRA1 SNP rs3802890 was associated with measures of sociality in a cohort of individuals with schizophrenia, and in a cohort of typical individuals, with significant effects limited to females in both populations. Different SNPs of AMBRA1 have also been linked with risk of schizophrenia, although sex differences were not investigated here [13].…”
Section: Introductionmentioning
confidence: 99%
“…Risk allele-carriers showed a higher blood oxygen level-dependent response in the prefrontal cortex during a flanker task, indicating that the risk allele is associated with impulsive-related traits [ 21 , 22 ] . Notably, a behavioral study on heterozygous Ambra1 mice (Ambra1 +/− ) revealed an autism-like phenotype that was restricted only to females [ 23 ] and a recent work proved an association between autism and intronic single nucleotide polymorphisms of the AMBRA1 gene in human female patients [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have revealed that female Ambra1 +/gt mice have some autistic features, but these are already apparent in young animals. Some of the analysed changes in the young animals however showed a slightly different characteristic in the middle aged mice, such as the form of induced seizures 53,54 , pointing towards a possible age related change. In our study we used a female to male ratio of 1:1 with an outbred CD1 background, whereas the studies showing autistic features were performed in Ambra1 +/gt with a C57BL/6N background and observations were only found in the female mice.…”
Section: Discussionmentioning
confidence: 95%